Urticarial eruption in COVID-19-positive children: A report of two cases - Shikhar Ganjoo; Resham Vasani (Our Dermatology Online, 2022)
Recent literature has reported a variety of dermatological manifestations in children and adults associated with COVID-19. Herein, we report urticarial eruptions in two COVID-19-positive children. In the first case, urticaria with angioedema preceded a febrile episode and only partially responded to conventional doses of antihistamines. In the second case, urticaria followed the appearance of fever and upper respiratory symptoms. Both cases recovered completely within two weeks of diagnosis. These cases demonstrate that urticaria and angioedema, precedent or following a febrile illness, with or without respiratory symptoms, may be a presenting symptom of COVID-19 infection in children. A high index of suspicion in such cases helps the early administration of treatment and isolation of the patients to limit the spread of the virus.